JAVANESE ISLAM AND GLOBALIZATION: A STUDY ON THE SUSTAINABILITY THE ABOGE ISLAM COMMUNITY IN INDONESIA - M Ali Sofyan; Tri Wahyuni; Win Listyaningrum Arifin (Jurnal Sosiologi Reflektif, 2023)
The indigenous religion of Java has a longer historical existence compared to the currently recognized state religions. Similarly, Javanese Islam has evolved through religious syncretism with Javanese culture. Javanese Islam has served as a means to reconcile the two opposing poles of this entity, as well as a way to attract followers. Aboge Islam in Purbalingga, Central Java is one form of Javanese Islam. The existence of Aboge Islam is facing increasing threats, particularly in the era of globalization. This article will provide an overview of the current reality, obstacles, and threats faced by the Aboge Islamic community, and discuss their future. This research is conducted using the qualitative ethnographic method. Data was collected through in-depth interviews with members of the Aboge Muslim community, as well as observations and document studies. The findings revealed that the Aboge Muslim community has undertaken various adaptation processes as a survival strategy to maintain its existence amidst the challenges posed by globalization. This form of adaptation is the inheritance of community values by passing down their traditional values to the younger generation, which includes 'ngormati leluhur' (the practices of ancestor worship), "melu gawe" (a Javanese term for working together), and "Turki" (Tuturan Kaki, oral transmission of knowledge and advice from parents or elders). Through this process, they hope their community will survive in the future.Religi lokal di Jawa memiliki usia lebih tua dari agama yang sekarang diakui oleh negara. Begitu juga Islam Jawa yang merupakan hasil sinkretisme religi dengan kultur Jawa. Islam Jawa menjadi jalan untuk mendamaikan dua kutub ekstrim entitas ini, sekaligus sebagai ‘jalan’ untuk mendapatkan pengikut. Islam Aboge di Purbalingga Jawa Tengah merupakan salah satu bentuk dari Islam Jawa tersebut. Keberadaan Islam Aboge semakin hari kian terancam terutama di era globalisasi. Tulisan ini akan menguraikan keberadaan komunitas Islam Aboge di masa depan, dengan melihat realitas, hambatan dan ancaman yang terjadi sekarang. Penelitian ini dilakukan dengan menggunakan metode kualitatif etnografi. Teknik pengumpulan data dilakukan melalui wawancara mendalam terhadap pemeluk Islam Aboge, observasi, dan studi dokumen. Hasil penelitian menunjukkan bahwa untuk menjaga eksistensi komunitasnya di tengah pusaran globalisasi, mereka telah melakukan sejumlah proses adaptasi sebagai pilihan untuk bertahan. Bentuk adaptasi tersebut adalah pewarisan nilai-nilai komunitas melalui pengajaran kepada anak-anak mereka, seperti ngormati leluhur, melu gawe, dan Turki (Tuturan Kaki, nasehat orangtua). Melalui proses ini mereka berharap komunitas mereka akan tetap bertahan di masa depan.